A Single Platinum Microelectrode for Identifying Soft Drink Samples - Lígia Bueno; Thiago R. L. C. Paixão (International Journal of Electrochemistry)
Cyclic voltammograms recorded with a single platinum microelectrode were used along with a non-supervised pattern recognition, namely, Principal Component Analysis, to conduct a qualitative analysis of sixteen different brands of carbonated soft drinks (Kuat, Soda Antarctica, H2OH!, Sprite 2.0, Guarana Antarctica, Guarana Antarctica Zero, Coca-Cola, Coca-Cola Zero, Coca-Cola Plus, Pepsi, Pepsi Light, Pepsi Twist, Pepsi Twist Light, Pepsi Twist 3, Schin Cola, and Classic Dillar’s). In this analysis, soft drink samples were not subjected to pre-treatment. Good differentiation among all the analysed soft drinks was achieved using the voltammetric data. An analysis of the loading plots shows that the potentials of −0.65 V, −0.4 V, 0.4 V, and 0.750 V facilitated the discrimination process. The electrochemical processes related to this potential are the reduction of hydrogen ions and inhibition of the platinum oxidation by the caffeine adsorption on the electrode surface. Additionally, the single platinum microelectrode was useful for the quality control of the soft drink samples, as it helped to identify the time at which the beverage was opened.